Incorporating Thinking Skills Theories in Indonesian EFL Classrooms - Zahratul Aeni; Zurina Khairuddin (EDULANGUE, 2022)
In responses to the demand of the twenty-first century learning, the Indonesian government stipulated the 2013 curriculum in order to prepare students to be more productive, creative, and innovative. The presence of English language subjects in secondary schools aims to develop students' communicative competence and instill the nation character’s noble values in life to increase the country's competitiveness in a global society. It can be realized by implementing learning embodied with critical and creative thinking skills in various language learning environments. This study aims to explore how the teachers apply the thinking skills theories (LOTS and HOTS) in teaching English language at secondary school in West Lombok. This qualitative case study research garnered the data through semi-structured interviews involving ten purposively selected English language teachers. The data were analyzed using thematic analysis through the process of coding, categorizing, and thematizing the data. The findings showed that the teachers lacked knowledge mastery to implement thinking skills (LOTS and HOTS) in teaching and learning of English language at secondary school in West Lombok. Though HOTS was very challenging, the teachers recognize that it is essential to implement it to achieve many benefits in the future. This study encapsulates that thinking skills (LOTS and HOTS) have not been efficiently incorporated into the classrooms. Recommendation for future research are discussed.